Pengaruh Shalat Dhuha terhadap Kedisiplinan Siswa Kelas V MI Islamiyah Pulak Segeran Indramayu - Amir Arifin; Frenky Mubarok; Fatimatuz Zahra (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research is motivated by the importance of instilling the character of discipline in students from an early age, especially at the elementary school level. One of the efforts to achieve this is through routine religious activities, such as the performance of the Dhuha prayer. As a sunnah prayer, Dhuha carries educational values that can foster attitudes of discipline, responsibility, and orderliness in daily life. The aim of this study is to determine the extent of the influence that performing the Dhuha prayer has on the discipline of fifth-grade students at MI Islamiyah Pulak Segeran. The study investigates several issues in the implementation of the Dhuha prayer, noting that some students are diligent in performing the prayer while others are less consistent. Therefore, the research questions are: How is the Dhuha prayer practiced? What is the level of student discipline? And, what is the influence of the Dhuha prayer on student discipline in class V at MI Islamiyah Pulak Segeran? This study is grounded in the objective of identifying the significance of the Dhuha prayer practice in shaping student discipline. This research employs a quantitative method using simple linear regression analysis. The population consists of all fifth-grade students at MI Islamiyah Pulak Segeran, with a sample of 46 students. The instrument used was a questionnaire to measure both the frequency of Dhuha prayer performance and the level of student discipline. Data were analyzed using SPSS software. The findings revealed a significance value of 0.001 < 0.05 and a coefficient of determination (R Square) of 0.208. This indicates that 20.8% of the variation in student discipline can be explained by the habit of performing the Dhuha prayer, while the remaining percentage is influenced by other factors. Thus, it can be concluded that the habit of performing the Dhuha prayer contributes to improving student discipline. Moreover, the implementation is regularly supervised by teachers, although it is not the sole determining factor. Based on the results, there is a positive influence of Dhuha prayer on the discipline of fifth-grade students at MI Islamiyah Pulak Segeran. Hence, the hypothesis is proven. It is expected that this thesis will serve as useful information and a reference for future research.